2006
DOI: 10.4315/0362-028x-69.9.2268
|View full text |Cite
|
Sign up to set email alerts
|

Leuconostoc carnosum Associated with Spoilage of Refrigerated Whole Cooked Hams in Greece

Abstract: A polyphasic taxonomic approach was used to identify a major atypical group of gas-forming, arginine-negative lactic acid bacteria associated with spoilage of whole (nonsliced) refrigerated (4 degrees C) cooked hams produced in two Greek industrial meat plants. Biochemical characterization revealed that the ham isolates shared their phenotypic properties with Leuconostoc carnosum, Weissella viridescens, and Weissella hellenica. However, gas chromatographic analysis of cellular fatty acids clearly differentiate… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
14
0

Year Published

2010
2010
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 21 publications
(14 citation statements)
references
References 31 publications
0
14
0
Order By: Relevance
“…The significantly different pathways between groups (Welch's t-test q < 0.01) are shown. (Samelis et al, 2006;Doulgeraki et al, 2010;Pothakos et al, 2015). Therefore, spoilage genera in the samples of groups 2, 3, and 4 could dominate by producing acid and, as a result, could be related to beef spoilage in beef meat.…”
Section: The Predicted Function Of the Beef Core Microbiotamentioning
confidence: 99%
“…The significantly different pathways between groups (Welch's t-test q < 0.01) are shown. (Samelis et al, 2006;Doulgeraki et al, 2010;Pothakos et al, 2015). Therefore, spoilage genera in the samples of groups 2, 3, and 4 could dominate by producing acid and, as a result, could be related to beef spoilage in beef meat.…”
Section: The Predicted Function Of the Beef Core Microbiotamentioning
confidence: 99%
“…Essential oils originating from oregano, thyme, basil, marjoram, lemongrass, ginger and clove were investigated in vitro (Barbosa et al, 2009) and on meat products (Burt, 2004;Fratianni et al, 2010) and found capable of affecting the growth and metabolic activity of foodborne microbiota (Skandamis and Nychas, 2001). Bacteriocins are microbial heat-stable peptides, active towards other bacteria (Gálvez et al, 2007); they are added as biopreservatives to improve the microbial stability and safety of chill-stored fresh and cooked meat (Samelis et al, 2006). In the EU, nisin (E234), a polypeptide produced by Lactococcus lactis, and natamycin (E235), produced by Streptomyces natalensis, are currently the only commercially available bacteriocins (Ercolini et al, 2010;Doulgeraki et al, 2012).…”
Section: Intrinsic Factors Composition and Antimicrobial Hurdlesmentioning
confidence: 99%
“…amelibiosum Aymerich et al, 2002;Hu et al, 2009) L. gelidum subsp. gasicomitatum (Korkeala and Björkroth, 1997) (Borch et al, 1996;Aymerich et al, 2002;Jaaskelainen et al, 2013) Sliced cooked ham Vacuum L. carnosum (Bjorkroth et al, 1998;Samelis et al, 2006;Nychas et al, 2008;Packaged Vasilopoulos et al, 2008;Krockel, 2013 al., 1988): sourness (LAB produce lactic and acetic acid during logarithmic and stationary phase of growth), gas formation (increase in CO2 concentration in packages during storage, attributed to metabolic by-products of the heterofermentative lactobacilli and Leuconostoc spp. ), slime and grey liquid (in some cases, the slime formation may be copious and unacceptable for selling; the amount increases with storage time and the appearance of the drip changes from transparent to white or grey ) and ropy slime formation (Borch and Nerbrink, 1989;Bjorkroth and Korkeala, 1997b).…”
Section: Packaging Strains Isolated Referencesmentioning
confidence: 99%
“…Therefore, to ensure the safety of stored food and reduce such risks, elucidation of the cold-adaptation mechanism of LAB in food products is important. LAB that are closely related to Leuconostoc mesenteroides , Lactococcus lactis , Leuconostoc citreum, and Weissella viridescens grow rapidly at temperatures below 10°C (Borch et al 1996 ; Chenoll et al 2007 ; Diez et al 2009 ; Hamasaki et al 2003 ; Metaxopoulos et al 2002 ; Samelis et al 2006 ; Samelis et al 1998 ), and are frequently isolated from spoiled cooked meat products stored at 10°C. These findings suggest a unique system of adaptation to low temperatures, causing rapid food spoilage in the refrigerator.…”
Section: Introductionmentioning
confidence: 99%